Menelisik Etika Hamba Tuhan di Ruang Digital:: Tafsir Kontekstual terhadap Efesus 5:15-16 - Yunus Hutagalung; Hasibuan, Serepina Yoshika (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract: This article aims to examine and construct a digital ethical foundation for God’s servants through a contextual interpretation of Ephesians 5:15–16. In today’s fast-paced digital environment, many ministers become entangled in the misuse of social media, hate speech, and self-promotion, damaging their spiritual credibility and the church’s witness. Using a descriptive qualitative method grounded in literature analysis, this study interprets the biblical text within its historical-theological context and connects it with contemporary digital realities. The findings highlight three key ethical principles: living wisely, managing time carefully, and maintaining moral awareness in an evil age. The novelty of this study lies in its contextual application specifically for God’s servants, contrasting with previous studies that addressed Christian ethics more generally. The theological implication is that the digital realm must be viewed as a sacred space for ministry, demanding ethical responsibility and spiritual discernment. Ministers are called to be digitally present in a way that reflects Christ’s character and advances His mission in the digital age. Abstrak: Artikel ini bertujuan untuk mengkaji dan membangun fondasi etika digital bagi hamba Tuhan melalui pendekatan tafsir kontekstual terhadap Efesus 5:15–16. Di era digital yang serba cepat dan penuh godaan, banyak hamba Tuhan terlibat dalam penyalahgunaan media sosial, ujaran kebencian, dan pencitraan diri yang berlebihan, yang berdampak buruk terhadap kesaksian pelayanan. Dengan menggunakan metode kualitatif deskriptif berbasis studi literatur, teks ditafsirkan dalam konteks historis-teologis dan dihubungkan dengan fenomena digital masa kini. Hasil penelitian mengidentifikasi tiga prinsip etis utama: hidup berhikmat, penggunaan waktu secara cermat, dan kesadaran moral terhadap zaman yang jahat. Kebaruan kajian ini terletak pada penerapan eksposisi kontekstual secara spesifik bagi hamba Tuhan, bukan sekadar umat Kristen secara umum. Implikasinya, kehadiran hamba Tuhan di ruang digital haruslah mencerminkan karakter Kristus dan bertanggung jawab secara etis dan spiritual. Dunia digital harus diperlakukan sebagai ladang pelayanan yang menuntut integritas, kebijaksanaan, dan kesadaran ilahi yang terus diperbarui.